1999
DOI: 10.1046/j.1439-0388.1999.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of evidence for bovine Y‐chromosomal variation in beef traits. A Bayesian analysis of Simmental data

Abstract: Materials and methods Correlations between sibs under autosomal, imprinted, and sex-linked inheritanceAll alleles of loci located on the autosomes are subject to recombination. This is also true for loci of the pseudo-autosomal region of the heterosomes. In the following all loci showing recombination are referred to as 'autosomal' loci without regard of their true location. U.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
3
6
0
Order By: Relevance
“…This is in good agreement with results from quantitative analyses of beef traits (Reinsch et al, 1999;Engellandt and Tier, 2002), who found no significant influence of y-chromosomal inheritance in cattle carcass traits. Neugebauer, Luther and Reinsch Jeon et al (1999), Nezer et al (1999) and Van Laere et al (2003) reported effects of a polymorphism of the imprinted IGF2 locus on carcass traits in pigs.…”
Section: Resultssupporting
confidence: 91%
“…This is in good agreement with results from quantitative analyses of beef traits (Reinsch et al, 1999;Engellandt and Tier, 2002), who found no significant influence of y-chromosomal inheritance in cattle carcass traits. Neugebauer, Luther and Reinsch Jeon et al (1999), Nezer et al (1999) and Van Laere et al (2003) reported effects of a polymorphism of the imprinted IGF2 locus on carcass traits in pigs.…”
Section: Resultssupporting
confidence: 91%
“…These results partially agreed with those reported by Engellandt and Tier (2002) and Neugebauer et al (2010) in Gelbvieh and Simmental cattle, respectively, although contradictory results were also available (Reinsch et al, 1999). The influence of the Y chromosome was previously highlighted by Kieffer and Cartwright (1968) and Schoeman (1989), who reported that even the morphology of this chromosome (i.e.…”
Section: Model Comparisonsupporting
confidence: 90%
“…Note that DIC estimates evidenced substantial departures when comparing independent chains from the same analysis (Table 2), although this variability did not contradict the final conclusions derived from average DIC estimate, and its standard error was smaller than 1% of the average DIC in all cases (Table 2). Moreover, the smallest effective chain lengths for genetic and residual variances were comparables to the values provided by other studies on sire-specific genetic variability in beef cattle (Reinsch et al, 1999).…”
Section: Model Comparisonsupporting
confidence: 84%
See 1 more Smart Citation
“…The convergence was determined by visual inspection of plots of realised parameter values against iteration number. Similar convergence detection was used by REINSCH et al (1999). Genetic correlations were estimated with a linear multivariate lactation model using the program VCE 4 (GROENEVELD, 1998).…”
Section: Methodsmentioning
confidence: 99%